Comparison of the efficacy of pioglitazone and metformin on ultrasound grade and liver enzymes level in patients with non-alcoholic fatty liver disease: A randomized controlled clinical trial - Khoshbaten, Manouchehr; Beheshtirouy, Samineh; Shayanrad, Shahrzad; Gharekhani, Afshin; Rezaee, Haleh (Drug Research, 2023)
Background This study aimed to evaluate the effectiveness of metformin and pioglitazone in combination with vitamin E on sonography grade and liver enzymes level in patients with non-alcoholic fatty liver disease.Methods A randomized controlled clinical trial was designed with 68 patients diagnosed with non-alcoholic fatty liver disease by sonography and clinical examinations. Sixty-eight patients were randomly divided into two groups; 34 were assigned to receive 15 mg of pioglitazone per day and 34 were assigned to receive 1000 mg of metformin per day for 6 months. All of the patients received vitamin E at a dose of 800 IU daily for six months. The sonography grade of fatty liver and the levels of alanine aminotransferase and aspartate aminotransferase of patients were evaluated at baseline, and within three and six months after initiation of the intervention.Results The use of metformin or pioglitazone in combination with vitamin E decreased the sonography grade of non-alcoholic fatty liver disease patients after 6 months of treatment (p-value<0.05); however, patients in metformin group benefit more compared to pioglitazone group. Patients who received metformin and vitamin E had a significant reduction in the levels of alanine aminotransferase and aspartate aminotransferase (p-value<0.05). There were no significant changes in the liver enzymes level of the patients who received pioglitazone and vitamin E (p-value>0.05).Major conclusion The concomitant use of metformin and vitamin E significantly improves the sonography grade of fatty liver and the level of liver enzymes in patients with non-alcoholic fatty liver disease.
Keywords: Non-alcoholic fatty liver disease; NAFLD; pioglitazone; metformin; ALT; AST